2001
DOI: 10.1016/s0014-5793(01)02156-1
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of endonuclease III protects Escherichia coli mutants defective in alkylation repair against lethal effects of methylmethanesulphonate

Abstract: Endonuclease III of Escherichia coli is normally involved in the repair of oxidative DNA damage. Here, we have investigated a possible role of EndoIII in the repair of alkylation damage because of its structural similarity to the alkylation repair enzyme 3-methyladenine DNA glycosylase II. It was found that overproduction of EndoIII partially relieved the alkylation sensitivity of alkA mutant cells. Site-directed mutagenesis to make the active site of EndoIII more similar to AlkA (K120W) had an adverse effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Saci_0385 codes for 3-hydroxy-isobutyrate (HIB) dehydrogenase, which is involved in valine degradation (38,41). The annotated, upregulated genes include Saci_1497, encoding endonuclease III, which is involved in DNA repair (15), and Saci_1494, encoding a type II/IV secretion system protein suspected to be involved in archaeal flagellar synthesis (Table 2). These differentially expressed genes provided little information about the likely mechanism or regulation of simultaneous metabolism of glucose and xylose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saci_0385 codes for 3-hydroxy-isobutyrate (HIB) dehydrogenase, which is involved in valine degradation (38,41). The annotated, upregulated genes include Saci_1497, encoding endonuclease III, which is involved in DNA repair (15), and Saci_1494, encoding a type II/IV secretion system protein suspected to be involved in archaeal flagellar synthesis (Table 2). These differentially expressed genes provided little information about the likely mechanism or regulation of simultaneous metabolism of glucose and xylose.…”
Section: Resultsmentioning
confidence: 99%
“…The others that were upregulated mostly encoded hypothetical proteins, many of which are conserved only in Sulfolobus species or archaea. Some of the few annotated genes coded for proteins like endonuclease III (Saci_1497), which is involved in DNA repair (15), and type II/IV secretion system protein (Saci_1494), which is likely involved in flagellar biosynthesis. The relevance of these proteins to simultaneous catabolism remains unknown, and the absence of well-annotated orthologs of the differentially expressed genes made it difficult to assign a function to them.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro the Fpg and Nth proteins can cleave dR via b-elimination with high ef®ciency (66,67) and may participate in repair of AP sites. However, it was shown that fpg and nth, in contrast with xth and xth nfo mutants, are not sensitive to alkylation DNA damage, suggesting that DNA glycosylases/AP lyases play a minor role in repair of AP sites in vivo (70,71). Interestingly, we found a signi®cant 5-fold increase of dRinduced reversion frequency in E.coli fpg nth mutant, suggesting that the DNA glycosylases/AP lyases suppress mutations induced by dR in vivo.…”
Section: Discussionmentioning
confidence: 62%